2011
DOI: 10.1007/s11069-011-9729-4
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of probable paleotsunami deposits on Kho Khao Island, Phang Nga Province, Thailand

Abstract: The 2004 tsunami deposits and probable paleotsunami deposits were studied at the southern Kho Khao Island, on Andaman Sea coast of Thailand. The 2004 tsunami laid down about 8 cm of fining upward medium sand and locally about 40 cm of massive coarse sand with common mud clasts. The sediments were characterized by the presence of marine foraminiferal assemblage; however, already after 5 years many of carbonate foraminiferal tests were partly or completely dissolved. The probable paleotsunami deposits form layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 31 publications
0
15
1
1
Order By: Relevance
“…The published results include works focused on the overall geological impacts of the tsunami Choowong et al, 2007;Kelletat et al, 2007;, on the detailed analyses of sedimentary prop-erties of sandy deposits (Hori et al, 2007;Choowong et al, 2008a, b;Fujino et al, 2008Fujino et al, , 2010Goto et al, 2008;Matsumoto et al, 2008;Alam, 2010;Naruse et al, 2010) and on the boulder deposits (Goto et al, 2007;Yawsangratt et al, 2009). Also studied were specific aspects such as the micropaleontological features of the deposits (Hawkes et al, 2007;Kokociński et al, 2009;Sawai et al, 2009;Yawsangratt et al, 2012), their geochemistry (Szczuciński et al, 2005;Boszke et al, 2006;Kozak et al, 2008;Zioła-Frankowska et al, 2009), their physical properties (Bishop et al, 2005) and their mineralogy . The IOT deposits were also presented in papers focused on paleotsunami deposits (Jankaew et al, 2008Fujino et al, 2009;Brill et al, 2011;Yawsangratt et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The published results include works focused on the overall geological impacts of the tsunami Choowong et al, 2007;Kelletat et al, 2007;, on the detailed analyses of sedimentary prop-erties of sandy deposits (Hori et al, 2007;Choowong et al, 2008a, b;Fujino et al, 2008Fujino et al, , 2010Goto et al, 2008;Matsumoto et al, 2008;Alam, 2010;Naruse et al, 2010) and on the boulder deposits (Goto et al, 2007;Yawsangratt et al, 2009). Also studied were specific aspects such as the micropaleontological features of the deposits (Hawkes et al, 2007;Kokociński et al, 2009;Sawai et al, 2009;Yawsangratt et al, 2012), their geochemistry (Szczuciński et al, 2005;Boszke et al, 2006;Kozak et al, 2008;Zioła-Frankowska et al, 2009), their physical properties (Bishop et al, 2005) and their mineralogy . The IOT deposits were also presented in papers focused on paleotsunami deposits (Jankaew et al, 2008Fujino et al, 2009;Brill et al, 2011;Yawsangratt et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Also studied were specific aspects such as the micropaleontological features of the deposits (Hawkes et al, 2007;Kokociński et al, 2009;Sawai et al, 2009;Yawsangratt et al, 2012), their geochemistry (Szczuciński et al, 2005;Boszke et al, 2006;Kozak et al, 2008;Zioła-Frankowska et al, 2009), their physical properties (Bishop et al, 2005) and their mineralogy . The IOT deposits were also presented in papers focused on paleotsunami deposits (Jankaew et al, 2008Fujino et al, 2009;Brill et al, 2011;Yawsangratt et al, 2012). The aforementioned works revealed that the IOT deposits varied considerably regarding extent, thickness, grain size (mud to boulders), internal structures, composition and preservation potential.…”
Section: Introductionmentioning
confidence: 99%
“…Sedimentary effects of recent tsunamis have been described from various locations (e.g. Szczuciński et al 2006;Goto et al 2007Goto et al , 2009Goto et al , 2011Paris et al 2009;Matsumoto et al 2010;Yawsangratt et al 2009Yawsangratt et al , 2012.…”
Section: Introduction -Palaeotsunami Studiesmentioning
confidence: 99%
“…This often results in an admixture of open shelf faunal elements in shallow-water deposits or in mixing of marine and terrestrial elements (Kaźmierczak and Goldring 1978;Bussert and Aberham 2004;Cantalamessa and Di Celma 2005;Paris et al 2009). Another feature is the common incorporation of ripped-up mud clasts within fine-grained deposits (Yawsangratt et al 2012) or, more generally, a bimodal character of the deposited material, with large clasts embedded within finer sediments (Cantalamessa and Di Celma 2005;Yawsangratt et al 2009). Some authors point to the association of tsunami deposits with other structures that can be attributed to seismic shocks, such as neptunic dykes or synsedimentary faults (Spaletta and Vai 1984;Pratt 2002), or with plastic deformations of the underlying sediments (Michalik 1997).…”
Section: Introduction -Palaeotsunami Studiesmentioning
confidence: 99%
“…3 Phra Thong Monecke et al, 2008Malik et al, 2011Yawsangratt et al, 201120 Martin et al, 2008MacInnes et al, 2010Peterson et al, 2008Luque et al, 2002, 2012 , 1995 …”
unclassified